Copper Deficiency Myelopathy After Upper Gastrointestinal Surgery. (14th December 2017) - King, Dominic; Siau, Keith; Senthil, Latha; Kane, Katherine F.; Cooper, Sheldon C.
Abstract: A well‐functioning alimentary canal is required for adequate nutrient absorption. Disruption to the upper gastrointestinal tract through surgery can lead to micronutrient malnourishment. Copper deficiency has been noted in up to 10% of those undergoing Roux‐en‐Y gastric bypass surgery, but sequalae are not frequently reported. The resultant deficiency states can have profound and long‐term consequences if not realized early and managed appropriately. Here we present a case of copper deficiency myelopathy, a condition indistinguishable from subacute combined degeneration of the spinal cord, following upper gastrointestinal bypass surgery for gastric ulceration, further complicated by inadequate nutrition.